PENGARUH PENILAIAN KINERJA TERHADAP MOTIVASI DAN PRODUKTIVITAS KERJA KARYAWAN PADA HOTEL PANGRANGO 2 BOGOR - Janusi Waliamin (Universitas Prof. Dr. Hazairin SH, 2020)
The hotel business in the city of Bogor has increased from year to year which has increased business competition. Then it is followed by a performance appraisal of employees whose aim is to monitor and maintain the performance of the selected employees because the performance appraisal will affect the follow-up needed by the employees relating to staffing decisions, for example promotion, payroll, or development. Based on this, this study aims to analyze the effect of performance appraisal on employee motivation and work productivity at the hotel pangrango 2 in Bogor.This type of research used in this study was a quantitative approach or statistical data analysis. The data sources were obtained from distributing questionnaires to 133 employees. The validity of the data was analyzed using the Product Moment Pearson correlation technique formula while the reliability of the measuring instrument was carried out using the Alfa Cronbach technique. The results showed that the employees of the Hotel Pangrango 2 Bogor used self-appraisal techniques, the effect of evaluation on motivation had a positive effect, the place of evaluation had no effect on employee motivation, the evaluation method on motivation had a negative effect, and motivation had a positive effect on the employees’ work productivity. Based on the results of the analysis of the research, the Hotel Pangrango 2 Bogor really needs to pay attention to performance evaluation factors because it is very influential on employee motivation and motivation itself will affect employees’ performance productivity.